2009
DOI: 10.12693/aphyspola.116.340
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR/PAS Studies of Cu(II)-EDTA Complexes Sorption οn the Chelating Ion Exchangers

Abstract: The possibility of removal of copper(II) complexes with ethylenediaminetetraacetic acid (EDTA) from waters and wastewaters by the chelating ion exchangers Lewatit TP 214, Lewatit TP 260 and Diaion CR-20 as well as the mechanism of their sorption onto them were investigated. In order to describe the sorption process of Cu(II) ions in the presence of EDTA, the FT-IR/PA spectra of the abovementioned chelating ion exchangers were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
(11 reference statements)
0
29
0
Order By: Relevance
“…In the literature many examples of Lewatit TP-214 application can be found, e.g. palladium(II) recovery from the HCl-NaCl [3] and HCl, HCl-HNO 3 solutions [4][5][6], copper sorption [7], selective removal of cadmium from a feed solution containing other metals including nickel (Ni) and/or cobalt (Co) [8], etc. The additional information concerning applicability of the resins with the functional thiourea and isothiourea groups in noble metal ions separation and recovery can be found in [9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature many examples of Lewatit TP-214 application can be found, e.g. palladium(II) recovery from the HCl-NaCl [3] and HCl, HCl-HNO 3 solutions [4][5][6], copper sorption [7], selective removal of cadmium from a feed solution containing other metals including nickel (Ni) and/or cobalt (Co) [8], etc. The additional information concerning applicability of the resins with the functional thiourea and isothiourea groups in noble metal ions separation and recovery can be found in [9,10].…”
mentioning
confidence: 99%
“…In the case of HCl [2], HCl-NaCl [1], H 2 SO 4 , NH 4 OH [11] solutions similar observation was not made. Additionally, in the papers [1][2][3][4][5][6][7][8][9][10][11][12] neither of the authors observed and mentioned the ion exchange resin functional groups degradation in the HCl -noble metal system. Moreover, this resin is applied on a large scale which indicates that its groups must be stable to be efficient.…”
mentioning
confidence: 99%
“…The increased intensity and broadness of the SO 3 À and C‚O peaks of the resin loaded with Cu 2+ and Cd 2+ ( Fig. 2c and d) indicated the adsorption of the metal ions (Kolodynska et al, 2009). …”
Section: Characterization Of Synthesized Materials Using Ftirmentioning
confidence: 90%
“…The palladium coordination over the modified silica gel matrix was studied by means of adsorption essays and completed with the theoretical studies showing that the most likely coordination model could be through sulfur or hydrogen in the thiouronium group, the modified silica gel/Pd (II) relation 2/1, being the model 7 the most likely. Since the thiournonium group modified silica gel and the adsorbed Pd (II) do not show an ionic interaction due to the stability of the adsorbed metal toward pH variations [7][8] that mechanism was discarded.…”
Section: Discussionmentioning
confidence: 99%
“…The thiouronium group has been used in organic resins for the recuperation of metals with added value [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%